The political economy of regulations and trade: Wine trade 1860–1970. (24th April 2018) - Meloni, Giulia; Swinnen, Johan
Abstract: Dramatic changes in the 1860–1970 wine trade provide insights on the political economy of regulations and policy instrument choice and trade. An invasion of Phylloxera in the 1870s turned France from the world's leading exporter to a massive importer of wine and grapes. When French production recovered a combination of tariffs, safety regulations and quality standards were introduced to protect its French producers, causing dramatic changes in global wine and grape production and trade, including in Spain, Italy, Turkey, Greece, Algeria, Tunisia and Morocco. Changes in wine regulations were caused by relative income and loss aversion factors in political economy. Tariffs were the preferred policy instruments as they directly restrict imports, bring in revenues, have low transaction costs and are preferred political instruments when there are information imperfections. Safety regulations and quality standards, including labelling and input prohibitions, reduce asymmetric information for consumers or undesirable externalities, and simultaneously protected domestic producers. Regulations were often targeted at imported products (wine and raisins) when tariffs were ineffective or constrained by institutions (such as on colonial wine). Hence, tariffs and quality regulations were jointly used in wine policy, both as complements and as substitutes in policy design.